Jump to content

  • Log in with Facebook Log in with Twitter Log In with Steam Log In with Google Sign In
  • Create Account




- - - - -

Simultanous equations

Posted by F257, 21 September 2009 · 431 views

It seems somone on this server is very fond of procreational activites.I owuld have posted something in dediction but not allowed to post pornographic materail instead so ...


Spoiler


Re-edited for clearing confusion.Danke Phantasm :)




ugh.. you lost me. And I'm kind of good with math... is this supposed to be funny?
lol no i just had spare time to waste before whatever i wanted to watch on telly come :P Which part you lost on? I actually manged to learn this myself from some website a long time ago. Havent done it in ages but can work it out
lol wait you can use this

http://www.hellam.ne...bra/simul1.html

its great :)

Ok look at

http://www.bbc.co.uk...oushirev1.shtml

_______________________________________________________________________________________
Its probaley clearer on the link but....

Solve these simultaneous equations and find the values of x and y.

* Equation 1: 2x + y = 7
* Equation 2: 3x - y = 8


As you can see they are already in the format ax +by = c

And also the Y coefficent is already matched up. Since the two coeffiecentsa are different you need to add

Add the two equations to eliminate the ys:

* 2x + y = 7
* 3x - y = 8
* ------------
* 5x = 15
* x = 3



Now you got x =3, put into equation 1 (as i state in the guide above, not in the link. its the same results either way but i like to double check)

Equation 1 ) 2x + y = 7

2 x 3 + y = 7

6 + y = 7
y=1

Equation 2 ) 3x - y = 8

3 x 3 - 1 = 8

It works so

X = 3, Y =1
Scroll to the bottom an you 'll see they havent arranged

[quote]Equation 1: y - 2x = 1

Equation 2: 2y - 3x = 5[/quote]

Into the ax +by = c format but you can

[quote]Equation 1: -2x +y = 1

Equation 2: -3x +2y = 5[/quote]

Now if we multipoly equation 1 by 2 to make coefficent of Y to match up

[quote]Equation 1: -4x +2y = 2

Equation 2: -3x +2y = 5[/quote]

This comes to


[quote] -x = -3

[/quote]

means

[quote]x =3 [/quote]

aubstitue into equation 1

[quote]Equation 1: 2 x 3 +y = 1
[/quote]

means

[quote]6 + y = 1[/quote]

rearange to

[quote]6 + 1 = y[/quote]

[quote]y = 7 [/quote]

[quote]

Equation 2: -3x +2y = 5[/quote]

to check this is correct put both y and x into equation 2

[quote]

Equation 2: -3 x 2 +2 x 7 = 5[/quote]

x = 3 , y =7 . same results as the link

(lol sorry ran out of the number of quotes im allowed :P)

Lol i was only ever good on this part of the course ^^ Hopeless at the graphs/quadractic's
OMFG .... I always hate math... blehhh

OMFG .... I always hate math... blehhh


I loved maths so much i took sn A lelvel in it even though i got all Us in my exams :P
Oops Sorry i thought I'm still in f|a forum for games... OK got it so my browser didn't clean old forum cache I visited last time by accident and talking about math :huh:
ROFL F25, i was sittin in math today, totally stuck on this, and i whipped out my laptop and started browsing the forums. Stumbled upon this gem, and now i understand!!!

God bless you =F|A= Priest :thanks

Oops Sorry i thought I'm still in f|a forum for games... OK got it so my browser didn't clean old forum cache I visited last time by accident and talking about math :huh:


lol well...maths can be fun :lol: And rofl val. Hope this works - dont blame me if it dosent, blame the BBC :P
O_O what the hell xD this is so simple solved in an other way xD

2x = 6 - 4y
-3 - 3y = 4x

take first equation and fint the x --> x = 3 - 2y

then substitute in the other equation --> - 3 - 3y = 12 - 8y

solve --> 5y = 15 --> y = 3

substitute in first equation --> 2x = -6 --> x = -3



and that's done :D


i use that method only when i 've got to do whith harder equations, like in analytic geometry when u gotta find common points between two circumferences or parables like this:

x^2 + y^2 + 5x + 6y + 13
x^2 + y^2 + 12x + 7y + 2

in that way u can get rid of squared terms and find x & y :D

O_O what the hell xD this is so simple solved in an other way xD

2x = 6 - 4y
-3 - 3y = 4x

take first equation and fint the x --> x = 3 - 2y

then substitute in the other equation --> - 3 - 3y = 12 - 8y

solve --> 5y = 15 --> y = 3

substitute in first equation --> 2x = -6 --> x = -3



and that's done :D


i like being awkwared :D
lol, this is pretty easy